Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation for example : -8-7x+-5(4)=0 . But the zero turned to -1 because a non zero constant never equals 0,but the problem doesn’t have a solution, but the answer is -1
Answer:
Lil Loaded, Jee hawkins 9lokknine
Step-by-step explanation:
Here is the equation: x+(x+20) = 120
Since you can't combine anything yet, its x+x+20=120
You need to get x by itself
Minus 20 from both sides
Its x+x=100 now
Combine the x's which is now 2x
Now divide 100 by 2 which is 50
x=50
---------------
Lets check:
50+(50+20)=120
Now combine the numbers in the parentheses
Its now 50+70=120
50+70=120 and 70-50=20
As you can see, he ran 50 minutes the first day and 70 minutes the second day